Understanding variability of the Southern Ocean overturning circulation in CORE-II models. (March 2018) - Downes, S.M.; Spence, P.; Hogg, A.M.
Highlights: Southern Ocean overturning circulation in twelve CORE-II models is assessed. Overturning circulation trends are linked to ocean stratification. Surface heat fluxes and eddy parameterization choice influence the ocean stratification. Abstract: The current generation of climate models exhibit a large spread in the steady-state and projected Southern Ocean upper and lower overturning circulation, with mechanisms for deep ocean variability remaining less well understood. Here, common Southern Ocean metrics in twelve models from the Coordinated Ocean-ice Reference Experiment Phase II (CORE-II) are assessed over a 60 year period. Specifically, stratification, surface buoyancy fluxes, and eddies are linked to the magnitude of the strengthening trend in the upper overturning circulation, and a decreasing trend in the lower overturning circulation across the CORE-II models. The models evolve similarly in the upper 1 km and the deep ocean, with an almost equivalent poleward intensification trend in the Southern Hemisphere westerly winds. However, the models differ substantially in their eddy parameterisation and surface buoyancy fluxes. In general, models with a larger heat-driven water mass transformation where deep waters upwell at the surface ( ∼ 55°S) transport warmer waters into intermediate depths, thus weakening the stratification in the upper 2 km. Models with a weak eddy induced overturning and a warm bias in the intermediate waters are more likely to exhibit larger increases in the upper overturning circulation, and more significant weakening of the lower overturning circulation. We find the opposite holds for a cool model bias in intermediate depths, combined with a more complex 3D eddy parameterisation that acts to reduce isopycnal slope. In summary, the Southern Ocean overturning circulation decadal trends in the coarse resolution CORE-II models are governed by biases in surface buoyancy fluxes and the ocean density field, and the configuration of the eddy parameterisation.